Acessibilidade arquitetônica: um estudo sobre as condições de estrutura física no Campus V da Universidade Estadual da Paraíba - Casimiro Júnior, José Rofrants Lopes (2023)
The general objective of the research is to evaluate the architectural accessibility conditions on Campus V - João Pessoa of the State University of Paraíba in the present day. It consists of initially analyzing the physical structure of Campus V of UEPB, considering the aspects inherent to architectural accessibility, also, verifying architectural accessibility in the context of external and internal legal regulations, including the IDP – Institutional Development Plan, as well collate the dimension of architectural accessibility through photographic records and current regulations. In this regard, the importance that accessibility occupies in higher education in the current scenario of institutional evaluation is undeniable, especially the social relevance of the study, since its results can contribute considerably to the reflection of the conditions of accessibility in higher education in Paraíba , such as proposing institutional actions and policies in the administrative, financial and budgetary management of educational institutions with a view to filling the probable gaps pointed out by the research. The methodological procedures used for the development of the research are classified as a qualitative approach of an applied nature, with scope and exploratory and descriptive objectives and a procedure based on bibliographical and documental analysis. With the results obtained, it was possible to propose guidelines the short, medium and long term referring to architectural accessibility in the ambit of Campus V of UEPB.